Theranostics in the Arab World; Achievements & Challenges - Al-Ibraheem, Akram; Abdlkadir, Ahmed; Albalooshi, Batool; Muhsen, Haider; Haidar, Mohamad; Omar, Yehia; Usmani, Sharjeel; al Kandari, Fareeda (Jordan Medical Journal, 2022)
In nuclear medicine, theranostics (combining therapy and diagnostics in one platform) is made possible through the utilization of radiopharmaceuticals for both therapeutic and diagnostic purposes by targeting one specific tumor receptor or certain molecular pathway. To make radiopharmaceuticals biologically relevant compounds, receptor ligands must be labeled with radionuclides. The possible applications are multifold and include: in vivo visualization of tumor biology; diagnosis and tumor staging; therapy planning and treatment of specific tumors. The application of theranostics results in giving the right treatment to the right patient at the right time, which is expected to improve therapeutic efficacy and increase overall compliance to therapy. For example, theranostics can be used to determine the heterogeneity of cancer lesions, which is one of the most difficult aspects of therapeutic success, allow the identification of patients who will benefit from therapy, avoid unnecessary conventional therapies, and implement salvage treatments for those who need them. The use of theranostics has seen unprecedented value for cancer patients in the last decade. Several radiopharmaceuticals are currently in use in clinical practice (e.g., [68Ga/177Lu] DOTATATE), while dozens more are still in the preclinical stages. The goal of this review article is to cover the current and future status of nuclear theranostics, particularly in the Arab world, with a focus on expanding the discipline beyond neuroendocrine tumors, castration-resistant prostate cancers, and differentiated thyroid cancers. Furthermore, representatives from different Arab countries were invited to describe their recent understanding and contributions to drive innovation in this evolving field.